Autonomía y autorregulación: aplicación de competencias en tecnología e informática (Papeles, 2012)
The present investigation was aimed at ascertaining the autonomy and self-regulation skills in a group of Grade 11 students Technical College District Julio Flórez in the subjects of technology and information. In order to identify the competencies was an experience in which students design on paper made robot prototype and subsequently digitized into a computer software; subsequently materialized in the technology workshop. Significant changes were noted in the attitudes of students and it was evident as between students stood and demanded performance goals according to the tasks imposed are obvious changes in the levels of regulation by students, these results are part of research in application of information technology researchers institutional educational knowledge allows modification in the teaching-learning methodologies.
Keywords: public art; community art; experimental workshop; research-creation; artistic methodology of project-based learning (PBL); strengthening the arts emphasis